LncRNA HOXA11-AS promotes glioma malignant phenotypes and reduces its sensitivity to ROS via Tpl2-MEK1/2-ERK1/2 pathway - Cheng Wei; Xiaoyang Zhang; Dazhao Peng; Xu Zhang; Haizhen Guo; Yalin Lu; Lin Luo; Bo Wang; Zesheng Li; Yingjie He; Xuezhi Du; Shu Zhang; et al. (Cell Death and Disease, 2022)
Abstract Our previous studies showed that dysregulation of the long noncoding RNA (lncRNA) HOXA11-AS plays an important role in the development of glioma. However, the molecular mechanism of HOXA11-AS in glioma remains largely unknown. In this study, we explore the molecular mechanisms underlying abnormal expression and biological function of HOXA11-AS for identifying novel therapeutic targets in glioma. The expression of HOXA11-AS, and the relationship between HOXA11-AS and the prognosis of glioma patients were analyzed using databases and glioma samples. Transcriptomics, proteomics, RIP, ChIRP, luciferase, and ChIP assays were used to explore its upstream and downstream targets in glioma. The role of HOXA11-AS in regulating the sensitivity of glioma cells to reactive oxygen species (ROS) was also investigated in vitro and in vivo. We found that HOXA11-AS was significantly upregulated in glioma, and was correlated with the poor prognosis of glioma patients. Ectopic expression of HOXA11-AS promoted the proliferation, migration, and invasion of glioma cells in vitro and in vivo. Mechanistically, HOXA11-AS acted as a molecular sponge for let-7b-5p in the cytoplasm, antagonizing its ability to repress the expression of CTHRC1, which activates the β-catenin/c-Myc pathway. In addition, c-Myc was involved in HOXA11-AS dysregulation via binding to its promoter region to form a self-activating loop. HOXA11-AS, functioned as a scaffold in the nucleus, also recruited transcription factor c-Jun to the Tpl2 promoter, which activates the Tpl2-MEK1/2-ERK1/2 pathway to promote ROS resistance in glioma. Importantly, HOXA11-AS knockdown could sensitize glioma cells to ROS. Above, oncogenic HOXA11-AS upregulates CTHRC1 expression as a ceRNA by adsorbing let-7b-5p, which activates c-Myc to regulate itself transcription. HOXA11-AS knockdown promotes ROS sensitivity in glioma cells by regulating the Tpl2-MEK1/2-ERK1/2 axis, demonstrating that HOXA11-AS may be translated to increase ROS sensitivity therapeutically.